2018
DOI: 10.1007/s11356-018-1844-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting congener profiles for persistent organic pollutants and PAH monitoring in European storm petrels (Hydrobates pelagicus) breeding in Ireland: a preen oil versus feathers approach

Abstract: Persistent organic pollutants (POPs) and polycyclic aromatic hydrocarbons (PAHs) are anthropogenic contaminants of environmental concern due to their persistence in the environment and capacity to accumulate in biota. Many of these contaminants have been found to have ill effects over wildlife and humans. Birds are known to be particularly affected through endocrine disruption and eggshell thinning. POPs have been banned or restricted through the Stockholm Convention (2001), making monitoring essential for tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Moreover, a similar congener pattern was found in both seabird species, with a predominance of BDE-47, BDE-99 and BDE-100 (Table 1). These compounds have been previously detected in feathers from others top predators including birds around the globe (Jaspers et al, 2007;Eulaers et al, 2011;Acampora et al, 2018;Monclús et al, 2018).The BDE-47 showed the highest values in CAP (< LOD -72.8 ng g −1 ) followed by BDE-99 and BDE100. These results are in line with those reported by Acampora et al (2018) (mean: 0.35 ng g −1 ; 0.46 ng g −1 ; 1.17 ng g −1 feathers, for BDE-47, BDE-99 and BDE-100, respectively).…”
Section: Persistent Organic Pollutantsmentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, a similar congener pattern was found in both seabird species, with a predominance of BDE-47, BDE-99 and BDE-100 (Table 1). These compounds have been previously detected in feathers from others top predators including birds around the globe (Jaspers et al, 2007;Eulaers et al, 2011;Acampora et al, 2018;Monclús et al, 2018).The BDE-47 showed the highest values in CAP (< LOD -72.8 ng g −1 ) followed by BDE-99 and BDE100. These results are in line with those reported by Acampora et al (2018) (mean: 0.35 ng g −1 ; 0.46 ng g −1 ; 1.17 ng g −1 feathers, for BDE-47, BDE-99 and BDE-100, respectively).…”
Section: Persistent Organic Pollutantsmentioning
confidence: 88%
“…Other reports from northern Europe have shown different distribution pattern of POPs for feathers, with a predominance of PCBs followed by OCPs and PBDEs (Jaspers et al, 2009;Acampora et al, 2018;Svendsen et al, 2018). Acampora et al (2018) reported mean levels of POPs in European storm petrels (Hydrobates pelagicus) breeding in Ireland. However, the ΣOCPs concentrations in CAP (mean: 48.06 ng g −1 feathers) were higher than those reported for the European storm petrel (mean: 17.9 ng g −1 feathers), while in BBA similar concentrations were observed (mean: 16.30 ng g −1 feathers).…”
Section: Persistent Organic Pollutantsmentioning
confidence: 89%
See 3 more Smart Citations